Pelaksanaan Bundle Chateter-Associated Urinary Tract Infections (CAUTI) Ketepatan Indikasi Pemasangan dan Pelepasan Kateter Urine - Sofia, Devi Rahma (Journal of Telenursing (JOTING), 2024)
This study aims to synthesize studies regarding the implementation of the CAUTI prevention bundle namely the accuracy of indications for installation and removal of urinary catheters. The method used is a systematic review by taking studies from four databases, namely Science Direct, SAGE, Pro Quest, and Scopus which were published in 2017-2022, and are in English. Selection uses PRISMA guidelines. The quality of the article is assessed using the critical appraisal instrument from JBI. There were 646 articles, but only 9 articles met the inclusion criteria. The results showed that in the implementation system, 5 studies used training for staff on accurate catheter placement, catheter care, or CAUTI prevention before or during the intervention. The instrument used is a form or sticker containing a reminder about the indication or removal of the catheter. Two studies used audit or feedback systems. Benefits in rate of insertion and duration of catheterization indicate a reduction in inappropriate catheter placement and a reduction in duration of catheter use. In compliance with the procedure, the accuracy of indications and urinary catheter removal showed increased compliance. And the CAUTI numbers show varying results. In conclusion, the bundle of indications for catheter insertion and removal can be applied and the results regarding implementation compliance are still limited. However, the effect on CAUTI rates needs to be compared with bundle interventions more fully. It could be considered research supervision and compliance with implementing the CAUTI bundle. Keywords: CAUTI bundle, CAUTI, Indications for urinary catheter installation, Urinary catheter removal, Infection prevention